2002
DOI: 10.1073/pnas.232580799
|View full text |Cite
|
Sign up to set email alerts
|

The A14–A43 heterodimer subunit in yeast RNA pol I and their relationship to Rpb4–Rpb7 pol II subunits

Abstract: A43, an essential subunit of yeast RNA polymerase I (pol I), interacts with Rrn3, a class I general transcription factor required for rDNA transcription. The pol I-Rrn3 complex is the only form of enzyme competent for promoter-dependent transcription initiation. In this paper, using biochemical and genetic approaches, we demonstrate that the A43 polypeptide forms a stable heterodimer with the A14 pol I subunit and interacts with the common ABC23 subunit, the yeast counterpart of the subunit of bacterial RNA po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…The Rpb7 Ortholog EЈ Stimulates Transcription at Low Temperatures by Catalyzing Open Complex Formation-The EЈ-F complex and its eukaryotic orthologs Rpb7/Rpb4 (RNAPII), Rpc25/Rpc17 (RNAPIII), and Rpa43/Rpa14 (RNAPI) form heterodimers that are a landmark of all non-bacterial RNA polymerases (33)(34)(35)(36)(37). The structure of the Rpb7/Rpb4 complex is very similar to the archaeal EЈF dimer structure (22,17) and to the RNAPIII counterpart of these subunits, C17/C25 (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The Rpb7 Ortholog EЈ Stimulates Transcription at Low Temperatures by Catalyzing Open Complex Formation-The EЈ-F complex and its eukaryotic orthologs Rpb7/Rpb4 (RNAPII), Rpc25/Rpc17 (RNAPIII), and Rpa43/Rpa14 (RNAPI) form heterodimers that are a landmark of all non-bacterial RNA polymerases (33)(34)(35)(36)(37). The structure of the Rpb7/Rpb4 complex is very similar to the archaeal EЈF dimer structure (22,17) and to the RNAPIII counterpart of these subunits, C17/C25 (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…We found that Ker1p shows 21% identity and 27% similarity to the 126-amino acid sequence of S. cerevisiae A14 and that the N-terminal 60 amino acids of Ker1p show especially high identity (37%) and similarity (43%) to S. cerevisiae A14. The N-terminal region also shows significant identity between the A14 subunits of S. cerevisiae and C. albicans (11), and Ker1p shows 26% identity and 36% similarity to the 132-amino acid sequence of C. albicans A14. The local identity of Ker1p to the S. cerevisiae and C. albicans A14 subunits is especially high (38 and 42%, respectively) between amino acids 42 and 65 of Ker1p, and this region contains a motif that may be conserved between the S. cerevisiae and C. albicans A14 subunits (SQLKRIQR), as already suggested by Peyroche et al (11).…”
Section: Co-immunoprecipitation Of Ker1p and Pol I-the Apparent Nuclementioning
confidence: 96%
“…Because RPA21 is an ortholog of A43 of S. cerevisiae, we re-examined the homology of Ker1p to S. cerevisiae A14, which heterodimerizes with A43. Previously, A14 was suggested to have homology to a putative open reading frame of IPF1568 from Candida albicans (11), suggesting that the A14 gene family is conserved in C. albicans, although no genetic or biochemical evidence was presented. This suggestion prompted us to directly investigate the homologies among Ker1p, A14, and IPF1568 (hereafter referred to as C. albicans A14), and Fig.…”
Section: Co-immunoprecipitation Of Ker1p and Pol I-the Apparent Nuclementioning
confidence: 99%
See 2 more Smart Citations